Development of a course module for signal processing associate to vibration measurement [compact disc] - 214626 Thong, Foong Yee (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006